Perkembangan dan Efektivitas Pelaksanaan Pengawasan Pengelolaan Dana Desa pada Inspektorat Daerah Kabupaten Batang Hari - Jasasila Jasasila (Ekonomis: Journal of Economics and Business, 2020)
The problem of this research is How the Development and Effectiveness of the Implementation of Village Fund Management in the Batang Hari District Inspectorate, with the aim of the research 1) To Know the Procedure of the Implementation of Village Fund Supervision carried out by the Batanghari Kabuaten Inspectorate 2) To Know the Development Findings of the Implementation of Village Fund Management Supervision in the Batang Hari Regency Inspectorate 3) To find out the level of effectiveness of the Implementation of Village Fund Management Supervision at the Batang Hari District Inspectorate. The type of data used in this study is a collection of information or facts that are recorded through direct observation while the data used is sourced from related agencies that are related to the research topic, the procedure for implementing the supervision of the writer is descriptive according to the data obtained, the authors also carry out an analysis using developmental analysis and effectiveness analysis. From the results of the analysis it was found that the greatest development of findings in 2017 was an increase of 6.81% from the findings of the previous year then in 2016 and 2017 there was a significant decrease which was down by 51.92% (2016) and in the year down 39, 37% from the previous year generally showed that the findings of the Village Fund in Batang Hari Regency during 2013 - 2017 tended to decrease, meaning that the supervision carried out by the Inspectorate of the Batang Hari Regency was already good. The implementation of Village Fund Supervision conducted by the Inspectorate on average during 2013-2017 shows that the achievement is quite effective with an effective ratio of 69.57%. Keywords: Procedure, Monitoring, Development, Effectiveness